The Relationship Between The Family Environment And The Incident Of Bullying At SDN 31 Bontoraja - Fitriani; Tenriwati; Ely Kurniati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Nothing new anymore. However, until now bullying incidents have not been handled specifically. While it is known that bullying is a trigger for violence against children. Violence is a form of action in the form of physical force, threats, or certain associations with the intention to hurt and cause physical or mental injury. Bullying is defined as intentional, aggressive, forceful oppression by individuals or groups. There are several factors that can influence the incidence of bullying in children, including the characteristics of the child itself. Objective: Knowing the relationship between the environment and the incidence of bullying at SDN 31 Bontoraja. Methods: This research is a quantitative study using an analytic observational design with a cross sectional approach. With a sample population of 41 and a sample of 41 people. This research uses a sampling technique, namely probability sampling using a simple total sampling technique which is also called simple. Results: In this study the results were obtained that for the low level of bullying there were 19 people and the high level of bullying was as many as 22 people. And the results of bivariate analysis using the chi-square test obtained results for the three independent variables, namely the level of age, gender, and family environment that H0 was accepted. Conclusions and suggestions: In this study it can be concluded that the family environment has no relationship with the incidence of bullying. Parents always control their children in socializing, using electronic and print media, for example parents taking their children to school, accompanying their children to watch television.